Hoya soidaoensis (Apocynaceae: Asclepiadoideae), a new species from southeastern Thailand - Kidyoo, Manit (Phytotaxa, 2013)
Hoya soidaoensis is proposed as a new species from Khao Soi Dao, Chanthaburi Province, Southeastern (SE) Thailand. This newly revealed species is thoroughly described, discussed and illustrated. This species is related to the common species H. caudata and H. flagellata, but they have quite different leaves, flowers and habitats.